Calcium coordination compounds based on phenoxyacetic acids: microwave synthesis, thermostability and influences on the crystal structures of chlorine substituent group on ligands. Issue 3 (1st February 2016) - Xu, Xiuling; Yan, Saisai; Hu, Fan; Zhao, Wei; Shuai, Qi
Abstract: Three calcium coordination compounds, [Ca(CPA)(H2 O)4 ]·(CPA), 1, [Ca(MCPA)2 (H2 O)2 ]·H2 O, 2, and [Ca(TCPA)2 (H2 O)3 ]·2H2 O, 3 [HCPA = 3-chlorophenoxyacetic acid, HMCPA = 2-methyl-4-chlorophenoxyacetic acid, and HTCPA = 2, 4, 6-trichlorophenoxyacetic acid], have been synthesized by the microwave method with advantages that include shorter reaction times, lower energy consumption, and higher product yield. The structures have been characterized by IR, elemental analysis, and single-crystal X-ray diffraction. Influences on the crystal structures by changing the number and position of chlorine substituent group in phenoxyacetic acid are discussed. Steric hindrance effects involving the Cl and an ability to form the O–H⋯Cl hydrogen bonds enrich the structure diversity. TG analysis reveals that the thermostability for the three compounds is3  > 1  > 2, which could be influenced by the existence of hydrogen bonds (O–H⋯Cl and O–H⋯O). Abstract :